Influence of desert sand and cooling regime on the compressive strength of high strength concrete after high temperatures - Zhang, M. H.; Liu, H. F.; Tian, S.; Ma, Y. C.; Doh, Shu Ing (IOP Publishing, 2020)
An experimental investigation is conducted to analyze the influence of desert sand replacement ratio and cooling regime on the compressive strength of desert sand-based high strength concrete (DS-HSC). According to the design of experiment, six desert sand replacement ratios (0%, 20%, 40%, 60%, 80% and 100%) are employed to concrete mixture. DS-HSCs are subjected to two cooling regimes (air cooling and water cooling) and various temperatures (20°C, 400°C, 500°C, 600°C, 700°C and 850°C, respectively) in this paper. The results indicate that the compressive strength of DS-HSC with air cooling is higher than that with water cooling. Moreover, the highest compressive strength appears with the desert sand replacement ratio of 20%. The compressive strength of DS-HSC gradually decreases with the increase of desert sand replacement ratio when the desert sand replacement ratio is more than 20%.